High acclimation potential in floating Macrocystis pyrifera to abiotic conditions even under grazing pressure – a field study. Issue 3 (24th April 2018) - Rothäusler, Eva; Reinwald, Hannes; López, Boris A.; Tala, Fadia; Thiel, Martin
Abstract : The persistence of floating seaweeds, which depends on abiotic conditions but also herbivory, had previously been mostly tested in outdoor mesocosm experiments. In order to investigate if the obtained mesocosm results of high seaweed persistence under natural environmental conditions and under grazing pressure can be extrapolated to field situations, we conducted in situ experiments. During two summers (2007 and 2008), Macrocystis pyrifera was tethered (for 14 d) to lines in the presence and absence of the amphipod Peramphithoe femorata at three sites (Iquique, Coquimbo, Calfuco). We hypothesized that grazing damage and seaweed persistence vary among sites due to different abiotic factors. By incubating the sporophytes in mesh bags, we were either able to isolate (grazing) or exclude (control) amphipods. To test for a mesh bag artifact, a set of sporophytes was incubated without mesh bags (natural). Mesh bags used to exclude herbivores influenced sporophyte growth and physiological performance. The chlorophyll a (Chl a ) content depended largely on grazers and grazed sporophytes grew less than natural and control sporophytes within the two summers. A decrease in Chl a content was found for the sites with the highest prevailing irradiances and temperatures, suggesting an efficient acclimation to these sea surface conditions. Our field‐based results of sporophyte acclimation ability even under grazing pressure widely align with previous mesocosm results. We conclude that M. pyrifera and other temperate floating seaweeds can function as long‐distance dispersal vectors even with hitchhiking mesoherbivores.